Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4067/s0717-95022011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Effects on Adrenal Cortex Cellular Proliferation in Pregnant Rats

Abstract: SUMMARY:Chronic stress by immobilization during pregnancy may cause alterations in mechanisms maintaining homeostasis in the adrenal gland. The objective of this study was to quantify cellular proliferation index in the adrenal cortex during pregnancy second half and assess the effects of chronic stress on it. Adrenal cortex proliferation index in stressed rats showed a significant decrease at 12 and 17 days of gestation, while at day 21 it did not show differences with the control treatments. Moreover, prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Ultrastructuraly, the cells showed electron-dense cytoplasm and the mitochondria showed disrupted cristae. These changes have been considered as signs of lowered functional activity of steroid-producing adrenal cells [27] and correlate well with adrenocortical overstimulation and /or degeneration [28,29] . Many circulatory disorders were expected as a result of compression of the hypertrophied cells on the sinusoidal capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructuraly, the cells showed electron-dense cytoplasm and the mitochondria showed disrupted cristae. These changes have been considered as signs of lowered functional activity of steroid-producing adrenal cells [27] and correlate well with adrenocortical overstimulation and /or degeneration [28,29] . Many circulatory disorders were expected as a result of compression of the hypertrophied cells on the sinusoidal capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…One of the distinctive findings observed in this study is the allocation of the proliferative cells at the junction of ZG and ZF and in the outer ZF. This finding may be explained according to one of the theories mentioned by (Bozzo et al, 2011) who reported that the cellular replacement in different adrenal cortical zones could be assigned to the transformation theory which proposed that the cells proliferate in an intermediate zone between ZG and ZF then the cells migrate towards both the capsule and the medulla.…”
Section: Advances In Animal Andmentioning
confidence: 81%
“…We also found that chronic stress in pregnant rats caused a reduction in proliferation (Bozzo et al 2011) and apoptosis in the adrenal cortex. Our results indicate a lower degree turnover of adrenal cortical cells.…”
Section: Chronic Stress and Adrenal Apoptosis 301mentioning
confidence: 87%
“…Earlier we demonstrated that the cell proliferation index (CPI) of the reticular zone in both control and experimental rats was signifi cantly decreased compared to the glomerular and fascicular zones for all three stages of gestation studied (Bozzo et al 2011).…”
Section: Declaration Of Interestmentioning
confidence: 98%